Development of Daruharidra (Berberis aristata) Based Biogenic Cadmium Sulfide Nanoparticles: Their Implementation as Antibacterial and Novel Therapeutic Agents against Human Breast and Ovarian Cancer - Bhatnagar A.; Mishra A. (My University, 2025)
Background: This article presents a new and environmentally friendly method for generating DH-CdSNPs (cadmium sulfide nanoparticles) ranging from 5-10 nm in size. A green synthesis method for the development of inorganic nanoparticles was developed a few years back for their applications in diverse fields, such as medicine, bioimaging and remediation. The biogenic synthesis of these nanoparticles containing daruharidra (Berberis aristata) and cadmium sulfide is an effective alternative. Aims: By employing Daruharidra extract as a herbal analog, we aim to minimize the risks and adverse effects that come along with the use of other chemically synthesized nanoparticles. This study's main goal was to investigate the potential of these nanoparticles as powerful antibacterial and anticancer agents. Methods: We used a crude powdered daruharidra extract as a stabilizer ingredient to create CdSbased nanoformulations in an environmentally responsible way. By exposing the breast cancer cell line (MDAMB-231) and ovarian teratocarcinoma cell line (PA1) to these nanoformulations, we were able to evaluate their anticancer activities. Additionally, flow cytometry analysis was conducted to scrutinize the process of cell cycle arrest and apoptosis in reference to anticancer studies. Furthermore, DH-CdSNPs were applied on different gram-positive as well as gramnegative bacteria in a disc diffusion assay to ascertain their antibacterial activity. Nanoparticles were tested on bacterial strains to check if they were resistant after the MIC or minimum inhibitory concentration. Results: The cytotoxicity of nanoparticles was tested by MTT assay. The impact of increasing concentrations of NPs on cell lines was tested, revealing a cytotoxic effect. The half-maximal inhibitory concentration values for a 24-hour treatment were determined to be 95.74µg/ml for ovarian cancer cells and 796.25 µg/ml for breast cancer cells. Treatment with DH-CdSNP resulted in a noteworthy increase in early apoptotic cells, with percentages rising from approximately 3% to 14.5% in ovarian cancer cell lines and from 4% to 13.6% in breast cancer cell lines. Furthermore, the NPs induced arrest of the cell cycle, specifically in the interphase of G2 and mitosis phase, with DNA damage observed in sub G1 in ovarian cancer cells and G0/G1 arrest observed in breast cancer cells. Additionally, the NPs exhibited exceptional potency against both gram-positive as well as gram-negative bacteria. Conclusion: Less research has been done on using bioinspired DH-CdSNP to deliver anticancer medications. The amalgamation of plant extract and the DH-CdSNP could cause a paradigm shift in the cancer therapy approach. The findings revealed that the biosynthesized DH-CdSNP limited the growth of human breast and ovarian cancer cells. This property can be further investigated against a variety of additional cell lines to determine whether this property makes the DH-CdSNP a promising treatment alternative. The results obtained from these nanoformulations exhibit faster efficacy compared to traditional medications. © 2024 Bentham Science.